PERAN TIM KERJA TERHADAP KINERJA KARYAWAN PERUSAHAAN PERBANKAN - Sri Hartini (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Performance in relation to the organizational society can be described as the level of achievement on the implementation of a particular task or the feedback process of previous performances in which causes enhancement on the future employee performance. In this present world of global organizational competition, rapid development is in such demand that raises complex continuous changes in every organizational aspect. In accordance with this principal, an organization is essentially required to have beneficial abilities such as competitive advantage in order to achieve success or to maintain a valuable image of the organizational productivity. Therefore, the objective of this research in correlation with the perception that teamwork has a great effect in the operational performances of an organization was to investigate the effect of teamwork on employee performance about the Palangka Raya branch employees of PT. Bank Rakyat Indonesia (state-owned enterprise) who continuously perform teamwork either in sales division, collection, or Account Saving Conscience (ASC).The research was conducted in both regression and correlation analyses. The regression analysis resulted in score < 0.05, showed that teamwork raises significant effects on the employee performance about the Palangka Raya branch employees of PT. Bank Rakyat Indonesia (state-owned enterprise). Meanwhile, on the correlation analysis the result showed the R score as 0.838 which can be inferred that there is a correlation between teamwork and the employee performance about the Palangka Raya branch employees of PT. Bank Rakyat Indonesia (state-owned enterprise) in an intensive and positive manner.